0372 Patient Perspectives of Sleep Disturbances on a Neurology Inpatient Unit. (25th May 2022) - Poulakis, Alexander; Ibarra, Michael; Lin, Jennifer; Wielgus, Oskar; Eisner, Lauren; McGauley, David; Kadura, Sullafa
Abstract: Introduction: Sleep is a process critical to our daily physical revitalization, but sleep in the hospital is often very disruptive and is associated with poorer health outcomes during recovery. We aimed to assess patient and staff perceptions on sleep disturbances on a neurology inpatient unit in order to minimize sleep disturbances during hospitalization. Methods: From April 2021 to November 2021, patients on a neurology inpatient unit completed Karolinska Sleep logs, Berlin questionnaires, and the Potential Hospital Sleep Disruptions and Noises Questionnaire (PHSDNQ). Surveys were administered three times a week to patients oriented, available to participate, and slept on the unit for at least one whole night. Responses were dichotomized and compared to previously-surveyed dichotomized disturbance perceptions by the unit staff. We used chi-square tests to analyze disturbances across both groups for statistical significance. Results: One hundred twenty-nine patient surveys were collected, and of the disturbances listed, bed comfort, general noise, vital signs, and toileting were the most significant disruptors to sleep. Staff agreed that noise was a top disruptor but ranked testing, pain, and medications higher than patients.High-risk patients for sleep apnea were more likely to be disturbed by medication administration than low-risk patients (19% vs. 7%, p=0.0288), with trends also nearing significance in neuro checks (17% vs. 7%, p=0.059) and light (17% vs. 7%, p=0.059).Overall, there were significant differences across almost all sleep disturbances when comparing the groups, with staff ranking noise, medications, testing, vital sign checks, neuro checks, anxiety, pain, light, and bed comfort significantly higher than patients (p<0.0001). Temperature was not statistically significant. While survey collecting, we found that patients reported specific interventions disrupted their sleep but later ranked them lower than we expected on PHSDNQ. Upon further questioning, patients thought those interventions were required by inpatient teams. Conclusion: There is undoubtedly room to minimize the top-ranked disruptors and identify discrepancies between high and low-risk sleep apnea patients. We found that patients typically expect certain sleep disturbances during hospitalization, and are generally unaware that we can modify them. Future studies should involve empowering patients to minimize sleep disruptions. Support (If Any):